Efeito do ângulo de impressão nas propriedades elétricas e mecânicas de peças poliméricas impressas em 3d - OLIVEIRA, Dhonata Sebastião Caldas (2019)
This work investigates the eect of FDM on the electrical and mechanical resistance of parts made of poly (lactic acid) (PLA) and poly (acrylonitrile-butadiene-styrene) (ABS). For this, the general aspects about polymers and some details about PLA and ABS are presented, as well as on printing methods such as stereolithography (SLA) and selective laser sintering (SLS), in addition to FDM. After that, the parameters used to print the test pieces, such as the format and dimensions of the three-dimensional model and the nozzle and table temperatures of the 3D printer and its print speed, are displayed. In addition, the electrical and mechanical characterization methods used, respectively, are shown by the two-point resistance measuring with a picoammeter and the maximum traction and deformation supported by the parts before breaking, with a tensile testing machine. These tests showed that PLA has greater resistance both electric and mechanical when printed at the angle of 0o, reaching peaks of 2; 94710; 0541 G And 62; 2694 MPa, respectively. In turn, ABS withstands traction better when printed at 90o, up to 30; 3704 MPa, and exhibits greater electrical resistance at 45o, up to 2; 6626 0; 0327G. Comparatively, PLA is superior to ABS in these two questions, but the latter proved to be more elastic, which we sought to explain briey based on the structures of these two polymers, due to the rubber phase inside the ABS polymer blend. Finally, the results indicate that the eects of printing parameters, such as printing angle, directly aect the physical properties of these polymers. Therefore, knowledge of these variables will be of great importance for fabrications of high performance parts in additive manufacturing.